Keberadaan Desa Wisata di Daerah Istimewa Yogyakarta - Rachmaniar (HUMANUS : Jurnal Sosiohumaniora Nusantara, 2024)
As is known, currently tourist villages can be used as an alternative choice when tourists visit the Special Region of Yogyakarta (DIY) even though in DIY itself there are many quite famous tourist attractions to visit. For this reason, a study of previous studies was conducted that discussed the existence of tourist villages in DIY. In order to answer this question, a literature study research method was used with research objects consisting of three empirical studies related to Kelor Tourism Village, Tembi Tourism Village, and Pentingsari Tourism Village. Data collection techniques in this study, namely by editing, organizing, and finding, with the results of the study being 1) there are tourist villages in DIY that do not yet have good enough tourist packages so that mentoring must continue to be carried out in order to be able to present unique and attractive forms of tourist packages; 2) tourist villages in DIY must continue to highlight their characteristics in order to have a clear identity so that it can facilitate branding and promotion that will be carried out; 3) based on the three empirical studies, it is known that tourist villages in DIY have not optimally utilized the use of the internet and social media to promote and brand their tourist attractions; and 4) tourism village managers in the Special Region of Yogyakarta need to be given training or workshops related to the use of the internet and social media.